2011
DOI: 10.1212/wnl.0b013e318211c39a
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the role of CXCL13 in Lyme neuroborreliosis

Abstract: CXCL13 shows high sensitivity and specificity for acute, untreated LNB. This novel marker appears to be helpful in clinically atypical cases and, in particular, in early stages of the disease when the B burgdorferi AI is (still) negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 20 publications
8
101
0
3
Order By: Relevance
“…However, multivariate multinomial logistic regression revealed that only CXCL13 significantly distinguished between clinically suspected and clinically evident Lyme neuroborreliosis (Table 3), but the odds ratio of 0.91 and 95% confidence interval (0.86 to 0.97) being close to 1 indicated the limited distinctive power of this marker. While our results corroborate previous findings that CXCL13 CSF concentration is the most useful diagnostic marker for Lyme neuroborreliosis (11,14,17,29), they show that it has a limited distinctive value.…”
Section: Discussionsupporting
confidence: 90%
“…However, multivariate multinomial logistic regression revealed that only CXCL13 significantly distinguished between clinically suspected and clinically evident Lyme neuroborreliosis (Table 3), but the odds ratio of 0.91 and 95% confidence interval (0.86 to 0.97) being close to 1 indicated the limited distinctive power of this marker. While our results corroborate previous findings that CXCL13 CSF concentration is the most useful diagnostic marker for Lyme neuroborreliosis (11,14,17,29), they show that it has a limited distinctive value.…”
Section: Discussionsupporting
confidence: 90%
“…They could be produced locally in the CNS or originate in the peripheral nervous system (PNS), especially in patients with BBB impairment [7,8,23].…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have revealed that the CSF CXCL13 chemokine levels in patients with LNB correlate with pleocytosis and decrease after the initiation of antibiotic treatment [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, PCR is not recommended for routine testing of CSF in Lyme disease CXCL13 -Although elevated concentrations of CXCL13, the chemokine B lymphocyte chemoattractant, are not unique to active nervous system Lyme disease, when combined with other diagnostic information, they might serve as a marker of disease activity or response to treatment (42). Like patients with neurosyphilis (43), patients with acute untreated nervous system Lyme disease and a CSF pleocytosis have elevated CSF concentrations of CXCL13 (44). Among 17 such patients, concentrations of CXCL13 were proportionately greater in CSF than in serum and were highly elevated in all CSF samples compared with the CSF of 178 controls without nervous system Lyme disease (mean 15,149 pg/mL versus 247 pg/mL) (44).…”
Section: Approach To Diagnostic Confirmationmentioning
confidence: 99%
“…Like patients with neurosyphilis (43), patients with acute untreated nervous system Lyme disease and a CSF pleocytosis have elevated CSF concentrations of CXCL13 (44). Among 17 such patients, concentrations of CXCL13 were proportionately greater in CSF than in serum and were highly elevated in all CSF samples compared with the CSF of 178 controls without nervous system Lyme disease (mean 15,149 pg/mL versus 247 pg/mL) (44). Five patients who had received at least two weeks of treatment for nervous system Lyme disease did not have substantially elevated CXCL13 concentrations (mean 202 pg/mL), whereas five patients who had been treated for less than two weeks had slightly elevated CXCL13 concentrations (mean 1412 pg/mL).…”
Section: Approach To Diagnostic Confirmationmentioning
confidence: 99%